The Use of the Past During the Last Military Dictatorship and Post-Dictatorship: The Holocaust as the Horizon of Identification, Alienation and Negotiation for the Jewish Community (Temas de Nuestra América Revista de Estudios Latinoaméricanos, 2016)
We live in an era in which the Holocaust has become a universal trope of historic trauma. The Nazi genocide has come to be known as the greatest disaster of civilization and, as such, simply mentioning it or comparing it to other repressive events stirs or blocks meanings about specific events. In the case of Argentina, the resonance of the memory of the Holocaust penetrated the origins of the most recent military dictatorship. As early as the year 1976, external voices that denounced the regime for perpetrating genocide were heard publically around the world. This article analyzes some uses of the Holocaust during the military dictatorship in Argentina, questioning the ways in which the memory of the Holocaust stirred or blocked feelings and the collective imagination on the repressive regime's practices.